Producing a Liquid Soap by Adding Lemon Extract from Used Cooking Oil for Multipurpose Cleaning Use - M. Kamal, Nurul Atiqah Aisyah; Ibrahim, Siti Aida (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The production of liquid soap from used cooking oil represents an innovative approach to waste management and household cleaning, and this study examines the feasibility of using this common household waste as a raw material for liquid soap production to reduce environmental pollution. Additives such as natural and synthetic can be also added into soap composition and will identify how much of the amount will effect the soap’s physicochemical properties. By incorporating natural additives like lemon extract, the liquid soap’s performance will be tested. The production process involves several stages: saponification, additive incorporation, and subsequent testing for pH, density and stain removal effectiveness. Results indicate that the pH for used and new cooking oil is 6 and 5 respectively. The density difference for both oil are as much as 0.33% which UCO having 0.912 g/cm³ and NCO is 0.909 g/cm³. Stain removal for soap performance were tested and all of the samples composition showing similarity in result. This shows that adding lemon extraction and using used cooking oil is comparable to using new cooking oil. By that, the aimed to achieve environmental pollution can be reduce. Overall, this study highlights the potential of repurposing used cooking oil into a sustainable product, providing a practical solution for both waste management and household cleaning needs.